A NEW APPROACH IN ELT : A LEXICAL STUDY - SWATHIVADLA, GRACE SHANIGARAM, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The lexical approach to language learning has gained prominence during the recent years. Its proponents believe that learning lexis has a crucial role to play in the classroom. But, text books, the only source of language are unable to provide the ESL learners with sufficient exposure to lexis. Hence, there is every need in including materials containing lexis in the curriculum. The present study proposes news bulletins as such materials. The objectives of the present article are fivefold: firstly,it gives a brief introduction to the lexical approach. Secondly, it describes the concept of lexis and its importance in language learning. Thirdly, it describes the significance of using news bulletins to learn lexis. Lastly, it enumerates a few lexisbased teaching tasks using news bulletins.